Modeling, Simulation and Proof-of-Concept of an Augmentation Ankle Exoskeleton with a Manually-Selected Variable Stiffness Mechanism - Shaikha F Abdulmajeed; Khaled S Al-Kaabi; Mohammad I Awad; Dongming Gan; Kinda Khalaf (Annals of Robotics and Automation - Peertechz Publications, 2020)
Despite its inherent complexity and wide dynamic variability, healthy human gait is distinguished by smoothness, stability and flexibility with minimal energy consumption. This is in part achieved by the human body's superb inherent joint compliance. In particular, the ankle joint plays an important role with its continuous variable stiffness, as compared to the stiffness of the knee and hip joints which remain nearly constant during the loading phases of the gait cycle. This paper presents a proof-ofconcept of a bio-inspired unpowered-compliant ankle exoskeleton designed to assist in human walking and reduce the biological demands of the calf muscle. An unpowered variable stiffness mechanism was developed and integrated onto the ankle exoskeleton to harness gait energy and enhance the ankle's biomechanical capabilities. The prototype was fabricated and validated on healthy subjects using preliminary experimental tests. The device uses a variable stiffness mechanism, which manually enables five levels of stiffness to replicate and compliment the human ankle's range of motion. A slider is triggered by a passive mechanical clutch, which controls spring engagement. By engaging different levels on the slider, the system produces five different levels of stiffness in the range of 0.8-4.7 N.m.rad-1. The ankle exoskeleton presented here offers a promising opportunity to adjust ankle compliance and improve the robustness of walking by providing users with further adaptability.